Pharmacological Treatment of Attention Deficit Hyperactivity Disorder (ADHD): A Systematic Review of Recent Data - Bellino, Silvio; Mirra, Marta; Brignolo, Elena; Bozzatello, Paola; Bogetto, Filippo (Current Psychopharmacology, 2014)
Attention-deficit/hyperactivity disorder (ADHD) is an impairing psychiatric disorder that affects not only children, but also adult patients. The symptoms of ADHD often produce an impairment of interpersonal functioning and educational performance with an increased school dropout risk. The aim of the present review is to provide an update of the empirical evidences of efficacy and safety that have been collected for stimulant and non-stimulant drugs in the treatment of ADHD patients. A systematic search of published randomized controlled trials of medications for ADHD was performed on the Pubmed and Cochrane databases from 2010 to 2013. Reviews and meta-analyses of older data were also examined. The first line drugs for ADHD without comorbidity or with comorbid conduct disorder are the stimulants methylphenidate (MPH) and dexmetylphenidate (d-MPH), available in immediate- and extended-release formulations. Other drugs with evidences of efficacy include both stimulants, such as amphetamines, and non-stimulants, such as atomoxetine and alpha agonists. A few non-stimulant agents, like reboxetine, have still limited data, but are under evaluation. Among the various treatment options, stimulants have generally demonstrated superiority compared to non-stimulants. Most of the studies are trials comparing methylphenidate, amphetamine and atomoxetine versus placebo, but comparison of active drugs is hindered by the absence of head-to-head works. Some meta-analyses have tried to overcome this problem, but further investigations directly comparing different active compounds are needed.
Keywords: Amphetamines